Kesetaraan Gender, Hierarki dan Jabatan Struktural dalam Budaya Akademik Perguruan Tinggi - Sartika, Didi; Nengsi, Ayu Rahma (Saree: Research in Gender Studies, 2022)
This study aims to reveal the phenomenon of gender equality in campus academic culture, the gender ratio in higher position holders, institutional patterns that are common in academic culture and classification based on symbolic power. The research was conducted using a mixed method, data was collected by distributing questionnaires to employees, for the sake of entering the data interviews were also conducted with selected informants. The collected data is analyzed by reducing, displaying data in tables and patterns, ending with drawing conclusions. The research findings show that in general there is no difference in treatment between men and women in their respective work departments based on the average recognition of 65% of male and female employees. The gender ratio in higher positions is dominated by men at 57.6% but this occurs naturally due to selection factors based on potential, programs carried out, leadership quality of the elected candidates. Gender inequality can be seen from the social conditions in the work environment based on the symbolic power of senior juniors where junior women get pressure from senior women in the academic culture in the work environment, especially in social communication and delegation of workload. AbstrakPenelitian ini bertujuan untuk mengungkap fenomena kesetaraan gender dalam budaya akademik kampus, rasio gender pada pemegang jabatan tinggi, pola-pola kelembagaan yang umum terjadi dalam budaya akademik dan klasifikasi berdasarkan kekuasaan simbolik. Penelitian dilakukan dengan menggunakan metode campuran, data dikumpulkan dengan menyebarkan kuesioner kepada karyawan, untuk kepentingan pemasukan data juga dilakukan wawancara dengan informan terpilih. Data yang terkumpul dianalisis dengan mereduksi, menampilkan data dalam bentuk tabel dan pola, diakhiri dengan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa secara umum tidak ada perbedaan perlakuan antara pria dan wanita di departemen kerja masing-masing berdasarkan pengakuan rata-rata 65% karyawan pria dan wanita. Rasio gender pada jabatan yang lebih tinggi didominasi oleh laki-laki sebesar 57,6% namun hal ini terjadi secara alamiah karena faktor seleksi berdasarkan potensi, program yang dijalankan, kualitas kepemimpinan dari kandidat yang terpilih. Ketidaksetaraan gender dapat dilihat dari kondisi sosial di lingkungan kerja yang didasarkan pada kekuatan simbolik senior junior dimana perempuan junior mendapatkan tekanan dari perempuan senior dalam budaya akademik di lingkungan kerja terutama dalam komunikasi sosial dan pendelegasian beban kerja.